2003
DOI: 10.1002/dvdy.10234
|View full text |Cite
|
Sign up to set email alerts
|

Development of transgenic chickens expressing bacterial β‐galactosidase

Abstract: Replication-defective retroviral vectors are efficient vehicles for the delivery of exogenous genes, and they may be used in the generation of transgenic animals. The replication-defective retroviral SNTZ vector carrying the lacZ gene with a nuclear localized signal was injected into the subgerminal cavity of freshly laid eggs. Subsequently, the eggs were allowed to hatch, and the chickens were screened for the lacZ gene by using the polymerase chain reaction. Eight of 15 male chickens that survived to sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 27 publications
3
66
2
3
Order By: Relevance
“…The modifications of the original procedures of Perry (1988) and Rowlett and Simkiss (1987) by Borwornpinyo (2000) resulted in 20% to 35% hatchability when used in conjunction with retroviral injections. The hatchability was sufficient to generate G0 roosters carrying the lacZ gene in their semen (Mozdziak et al, 2003). Currently, the windowing and the ex ovo culture are the only ways to introduce foreign DNA into a chicken embryo, and have viable offspring.…”
Section: Embryonic Manipulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The modifications of the original procedures of Perry (1988) and Rowlett and Simkiss (1987) by Borwornpinyo (2000) resulted in 20% to 35% hatchability when used in conjunction with retroviral injections. The hatchability was sufficient to generate G0 roosters carrying the lacZ gene in their semen (Mozdziak et al, 2003). Currently, the windowing and the ex ovo culture are the only ways to introduce foreign DNA into a chicken embryo, and have viable offspring.…”
Section: Embryonic Manipulationmentioning
confidence: 99%
“…Retroviral gene transfer techniques have been used the most frequently to generate transgenic chickens (Bosselman et al, 1989a(Bosselman et al, ,b, 1990Harvey et al, 2002a,b;Harvey and Ivarie, 2003;McGrew et al, 2003;Mozdziak et al, 2003), because high retroviral titers make it possible to transfer the gene of interest to many cells. Briefly, retroviruses have an RNA genome encased in a protein core containing integrase, reverse transcriptase, and protease.…”
Section: Retroviral Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The SNVbased vectors have been used in variety of embryonic chick tissues, such as the blastoderm, the primitive streak, the somitic and somatic mesoderm, epithelial heart tube, neural crest, vascular precursors, limb bud, central nervous system, and kidney primordium (Mikawa et al, 1992a,b;Mikawa and Fischman, 1992;Herzlinger et al, 1992;Epstein et al, 1994;Mima et al, 1995;Gourdie et al, 1995;Cohen-Gould and Mikawa, 1996;Mikawa and Gourdie, 1996;Itoh et al, 1996;Ong et al, 1998;Hyer et al, 1998Hyer et al, , 1999Cheng et al, 1999;Wei and Mikawa, 2000;Takebayashi-Suzuki et al, 2000;Das et al, 2000;Hatcher et al, 2001;Kanzawa et al, 2002;Ballard and Mikawa, 2002;Sugi et al, 2003). It has been shown that CXL and SNTZ are capable of infecting embryos as early as the prestreak stages (Wei and Mikawa, 2000;Mozdziak et al, 2003) and that the LacZ activity becomes detectable within 12-13 hr after infection (Wei and Mikawa, 2000). Coinjection of CXL and SNTZ has been used to assess clonal boundaries in lineage studies in the heart (Mikawa et al, 1992b).…”
Section: And Sntzmentioning
confidence: 99%